2015
DOI: 10.2486/indhealth.2015-0021
|View full text |Cite
|
Sign up to set email alerts
|

Job stress as a risk factor for absences among manual workers: a 12-month follow-up study

Abstract: This study was conducted to evaluate the impact of job stress on absence from work caused by illnesses and accidents through a prospective research design. A total of 2,349 manual workers were included in this analysis. In the first survey, job stress was determined using the Korean Occupational Stress Scale-Short Form. In the second survey, information on absence due to accidents or illnesses during the past one year was obtained through a questionnaire. The relationship was analyzed using a logistic regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 51 publications
1
15
0
1
Order By: Relevance
“… High-Income ( Lalive and Zweimüller, 2009 ) Cross-Sectional Age, education, year of conception, employment area, medical conditions during pregnancy, smoked during pregnancy, drank alcohol during pregnancy Adverse Pregnancy Outcomes Blue-collar women vs. other women The odds of congenital anomalies among female laboratory workers in an aluminum smelter were increased during employment as compared with women who gave birth prior to employment (OR = 7.89, 95% CI 1.16–53.77). The American Manufacturing Cohort Study (AMC) High-Income ( Sakr et al, 2010 ) Cross-Sectional Age, marital status, education, age at first sexual exposure, sources of knowledge on HIV/AIDS Use of condoms; sex with multiple partners; drug abuse Exposure-outcome among blue-collar women Among female garment workers, increased knowledge score was associated with increased odds of using a condom at last intercourse (OR = 1.482, p = 0.10), decreased odds of sex with multiple partners (OR = 0.832, p = 0.036), and decreased odds of drug abuse (OR = 0.766, p = 0.034). Female workers randomly selected from five garment factories in Dhaka, Bangladesh Lower-Middle-Income ( Sayem, 2010 ) Cross-Sectional Age, education, monthly income, occupation, marital status, health status, sexual norms and other behaviors, rural residency, communist party membership Lifetime multiple sexual partnerships Blue-collar women vs. other women C As compared with women in other occupations, the odds of having multiple sexual partners were increased among women in manual labor (OR = 3.347, 95% CI 1.069–10.476).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… High-Income ( Lalive and Zweimüller, 2009 ) Cross-Sectional Age, education, year of conception, employment area, medical conditions during pregnancy, smoked during pregnancy, drank alcohol during pregnancy Adverse Pregnancy Outcomes Blue-collar women vs. other women The odds of congenital anomalies among female laboratory workers in an aluminum smelter were increased during employment as compared with women who gave birth prior to employment (OR = 7.89, 95% CI 1.16–53.77). The American Manufacturing Cohort Study (AMC) High-Income ( Sakr et al, 2010 ) Cross-Sectional Age, marital status, education, age at first sexual exposure, sources of knowledge on HIV/AIDS Use of condoms; sex with multiple partners; drug abuse Exposure-outcome among blue-collar women Among female garment workers, increased knowledge score was associated with increased odds of using a condom at last intercourse (OR = 1.482, p = 0.10), decreased odds of sex with multiple partners (OR = 0.832, p = 0.036), and decreased odds of drug abuse (OR = 0.766, p = 0.034). Female workers randomly selected from five garment factories in Dhaka, Bangladesh Lower-Middle-Income ( Sayem, 2010 ) Cross-Sectional Age, education, monthly income, occupation, marital status, health status, sexual norms and other behaviors, rural residency, communist party membership Lifetime multiple sexual partnerships Blue-collar women vs. other women C As compared with women in other occupations, the odds of having multiple sexual partners were increased among women in manual labor (OR = 3.347, 95% CI 1.069–10.476).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies found decreased risk of all-cause and cause-specific mortality in blue-collar women as compared with women in the general population ( Gang et al, 2002 , Gissler et al, 2009 ), a finding which may reflect the fact that employed persons tend to be healthier on average as compared with members of the general population. Studies also find increased risk for various musculoskeletal disorders ( Hammarström et al, 2011 , Goldenhar et al, 1998 , Gold et al, 2006 , Hammar et al, 1994 , Hallman et al, 2015 , Grimmer, 1993 , Guendelman and Silberg, 1993 , Hall et al, 1993 , Gupta et al, 2014 ), adverse pregnancy-related outcomes ( Hanklang et al, 2014 , Hein et al, 2007 , Harley et al, 2010 , Heikkilä et al, 2008 , Hirokawa et al, 2013 , Heo et al, 2015 ), and smoking ( Cunradi et al, 2007 , Honjo et al, 2010 , Howard et al, 2017 , House, 1980 , Hocschild and Machung, 2012 ) in blue-collar women as compared with women in other occupations and job types.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also included several other potential confounding variables thought to be possibly associated with absence due to accident and illness. These potential confounders were selected based on the results of previous studies 26 , 27 ) . Employees provided information on age (yr), gender (male and female), education (middle school or lower, high school, and university), marital status (unmarried, married, and widowed/divorced), and duration of daily sleep (h).…”
Section: Methodsmentioning
confidence: 99%
“…MC and EL can also be an indication of underlying issues of work-related stress [ 20 ]. High job demands, organizational injustice and lack of reward are among the job stressors that relate to increased absence due to illnesses [ 21 ]. Nevertheless, work stressors specific to the job of nurses are seldom assessed for their associations with unplanned absenteeism.…”
Section: Introductionmentioning
confidence: 99%